Mastering financial calculations : a step-by-step guide to the mathematics of financial market instruments - Steiner, Bob (Financial Times Prentice Hall, 2007)
The new rebranded and updated edition of the bestselling hands-on practitioner¿s guide to the maths behind every key financial instrument and technique. Part of the renowned and hugely successful Mastering series. This is the definitive guide to exploring today's financial markets in a clear and comprehensive manner. Written by Robert Steiner, one of the UK's leading trainers for some of the world's largest financial institutions. The book includes essential course material and practice exercises for ACI qualifications This book has practicality-not theory-at its heart and is packed with real-world cases, worked examples and calculations. AUDIENCE: Practitioners are the primary market: traders, fund managers, corporate treasurers, programmers, accountants, and risk managers. Secondary are market students. This book will appeal to a huge audience. 1 in 10 people work in either banking, finance or insurance.